Stalkers and their victims - Mullen, Paul E. (Cambridge medicine, 2009)
Stalking : a problem behaviour -- Stalking as a social construction and social reality -- The epidemiology of stalking -- The victims of stalkers -- Stalking typologies and classifications -- The rejected stalker and the resentful stalker -- The predatory stalker -- Intimacy seekers and incompetent suitors -- The erotomanias and the morbid infatuations -- Stalking among juveniles -- Female stalkers -- Same gender stalking -- Cyberstalking -- Stalking by proxy -- The law as stalker's agent -- Stalking in the workplace -- Stalking of health professionals -- Stalking celebrities and other public figures -- False victims of stalking -- Evaluating and managing risk in the stalking situation -- The therapeutic approach to the stalker -- Reducing the impact of stalking on victims -- Defining and prosecuting the offence of stalking